Assessment of Relationship between Pain and Anxiety Following Dental Extraction—A Prospective Study - Sharma, Shalender; Majumder, Kaberi; Rao, J. K. Dayashankara; Arya, Varun; Siwach, Vijay; Gulia, Sunil (Scientific Research, 2015)
Objective—Anxiety and expected dental pain are the main reasons for avoiding any dental treatment by general population. In this study, we aimed to evaluate the various factors which can increase the anxiety and its association with pain perception of patients following dental extraction. Material and Methods—We had included 100 patients in our study who were undergoing orthodontic treatment and required extraction of either 34 or 44. Pain and anxiety levels after extraction were assessed with a visual analog scale (VAS) and an anxiety questionnaire consisting of eleven questions. Results—The mean VAS score for the entire study group was 16.23 ± 1.28 with statistically significant differences between genders, and was high in females and no statistically significant differences between different age groups. The mean anxiety score was 10.64 ± 3.12. This was significantly higher in women (P = 0.005), but there was no statistically significant differences between different age groups. There was a statistically significant correlation between VAS and total anxiety score (P < 0.001) as well as each question, except for question number 4, 8 and 9 in men. Conclusion—Although most patients had experienced limited pain, there was a significant gender difference in pain and anxiety level. They were anxious because they expected pain, women being more anxious than men. The most provoking factor for anxiety and pain while going for extraction in females was “being seated in dental chair”, while in men the most provoking factor was “uncertainty about proper numbness before extraction”.
Keywords: Dental Anxiety; Pain; Tooth Extraction